The molecular structure of hop latent viroid (HLV), a new viroid occurring worldwide in hops. - Puchta, H (1988)
A new viroid which does not seem to produce any symptoms of disease, and is therefore tentatively named hop latent viroid (HLV) was found to occur worldwide in hops. HLV proved to be infectious when mechanically inoculated onto viroid- and virus-free hops. The viroid nature of HLV was also substantiated by sequence analysis which revealed that HLV is a circular RNA consisting of 256 nucleotides, that can be arranged into the viroid-specific, rod-like secondary structure. HLV also contains the central conserved region typical for most of the presently known viroids. However HLV does not contain the viroid-specific oligo(A) stretch in the upper left part of its rod-like molecule. Because of this feature and a sequence similarity with the prototypes of the other viroid groups below 55%, HLV can be regarded as the first member of a new viroid group.